2013
DOI: 10.1167/iovs.12-11552
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Zinc for the Prevention and Treatment of Age-Related Macular Degeneration

Abstract: Citation: Vishwanathan R, Chung M, Johnson EJ. A systematic review on zinc for the prevention and treatment of age-related macular degeneration. Invest Ophthalmol Vis Sci. 2013;54:3985-3998. DOI:10.1167/ iovs.12-11552 PURPOSE. The objective of this systematic review was to examine the evidence on zinc intake from foods and supplements in the primary prevention and treatment of AMD.METHODS. Randomized controlled trials (RCTs), prospective cohort, retrospective cohort, and case-control studies that investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…A systematic review of these trials with zinc was published recently [76]. Ten studies were included: four randomized clinical trials, four prospective cohorts, and two retrospective cohort studies analyzing the effect of zinc intake, both from supplements and/or foods in the treatment and primary prevention.…”
Section: Zinc Supplementationmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of these trials with zinc was published recently [76]. Ten studies were included: four randomized clinical trials, four prospective cohorts, and two retrospective cohort studies analyzing the effect of zinc intake, both from supplements and/or foods in the treatment and primary prevention.…”
Section: Zinc Supplementationmentioning
confidence: 99%
“…The risk of visual acuity loss was of similar magnitude, but not statistically significant. Other two randomized clinical trials showed a statistically significant increase in visual acuity in early AMD patients and the other one revealed no effect of zinc treatment on visual acuity in advanced AMD patients [76]. Furthermore, results from the remaining six cohort studies on associations between zinc intake and incidence of AMD were inconsistent.…”
Section: Zinc Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…63 However, no apparent effect of lower-dose zinc on progression to advanced AMD was found in the latter AREDS2 study, 64 and current evidence on zinc intake for the prevention of AMD is inconclusive. 65 How zinc supplementation may help to slow down the progression of AMD is not quite understood, and an increase of zinc availability would have multiple effects. For instance, at intermediate and late stages of AMD, cellular zinc concentration could be lower as a result of the formation of a higher number of sub-RPE deposits and zinc supplementation might trigger uptake of zinc into the RPE-choroid complex, 66 helping to maintain the retinal functions.…”
Section: The Zinc-mt Redox Cycle and Its Potential Implication In Amdmentioning
confidence: 99%
“…Preincubation dramatically reduced the levels of hydrogen peroxideinduced protein and lipid peroxidation, and DNA damage in HLECs. Most, but not all, epidemiological studies have supported a role for L and Z in the prevention of cataract (see the recent review by Vishwanathan et al, 2013). The strongest link appears to be with nuclear cataract, and to a lesser degree, posterior subcapsular cataract (with little or no association to cortical cataract).…”
Section: Prevention Of Ocular Photodegradation Through Endogenous Andmentioning
confidence: 99%